Amended Soil Nutrients Enhance the Seed-Bearing Potential of Clones in a Clonal Seed Orchard of Teak (Tectona grandis Linn. f.) - Kumar, Pramod; Bhargav, Ragni; Patel, Pawan Kumar; Rana, P. K. (Indian Forester, 2023)
Clonal seed orchards of Teak (Tectona grandis Linn. f.) were established as a source of improved seeds to enhance productivity of plantations and increase economic returns. However, these orchards are not producing seeds sufficient to meet the demand mainly due to variation in flowering among clones of different ecological zones. The present study was carried out in a clonal seed orchard of teak established in Jabalpur, Madhya Pradesh, India. Clones were selected on their seed-bearing performance, either low seed producers or not producing seeds in preceding years. Nitrogen fertilizer alone and in combination with the phosphorus and potassium fertilizers were applied through soil drench in two split doses, before flowering, and before fruit set. Fertilizer application enhanced inflorescence and fruit density/seed-bearing potential considerably both in two consecutive years (2017 and 2018). Treatment of 543g/tree urea in combination with 240g/tree muriate of potash was most effective.Variation among treated clones showed inflorescence production up to 200% in 2017 and 167% in 2018 whereas; fruit production up to 750% in 2017 and 252% in 2018. Increased nutrient reserve enhances remobilization in 2018 at the time of reproductive phenoperiod significantly increasing seed-bearing potential of treated ramets. Amending soil in low seed producer clonal seed orchards of teak suitably with nitrogen fertilizer alone or in combination with the phosphorus or potassium fertilizer depending upon the nutrient availability status of orchard before the onset of flower and fruit set provides uniform distribution within the active root zone significantly contributing to reproductive growth and is recommended for enhancing seed production.